Knowledge, attitudes and practices on Tuberculosis (TB) among Radiographers in public hospitals in Klang Valley / Nurul Hazirah Mohthar - Mohthar, Nurul Hazirah (2015)
As number of Tuberculosis cases increase Health care workers (HCWs) tend to get more risk. It caused a greater concern among HCWs especially high risk group. HCWs are often dealing with potential infectious or positive Tuberculosis (TB) patients while undergo examination. Whenever there is potential exposure, action and prevention related this communicable disease towards high risk group must be considered and implement. OBJECTIVES: Study was conducted to determine the level of knowledge, attitudes and practices among radiographers in Klang valley. Moreover, in this research also, was carried out to assess relationship between knowledge, attitudes and practices on Tuberculosis (TB) among radiographer in Klang Valley. METHOD: This study was a cross-sectional study performed on Jan- March 2015.The respondents for this study only involved in six public hospitals. Total for respondents in this study were 184 of radiographers took part by using simple random sampling method. The tools for this study were based on structured questionnaires. Dichotomous questions used to measure the levels of knowledge. Meanwhile, Likert scale were use to determine the level of attitudes and practices. In addition, chi square test were used to see relationship between knowledge, attitudes and practices. RESULTS: In this study, most of the respondents received adequate knowledge related TB with 47.3%. Furthermore, attitudes of respondents were in moderate level with 54.9% of respondents that willing to change their attitudes while handling with TB patient. However, it was surprisingly found that level of practices among respondents with majority were high with 70.1%. Besides that, there were relationship between knowledge, attitudes and practices with 0.003 and 0.004 respectively. It was found that, number of working experience and their attitudes shown positive significant with p-value of 0.041. Also, knowledge and their working hours per day were identified showing that p-value of 0.049. CONCLUSION: Potential or positive PTB patients frequently coming for an examination to diagnose their health status in the hospitals. As HCWs especially radiographers frequently dealing with PTB patients they were in high risk or potential to be infected by this disease. Their KAP related TB is important for them to use and demonstrate as a barrier. Even though their knowledge and attitudes were in moderate levels, they tend to have good practices in TB infection control while handling with PTB patients. It was only some sort of stigmatization of their attitudes as well as their practices that driven an individual to follow the standard procedure related TB.